Oncometabolites‐driven tumorigenesis: From genetics to targeted therapy. Issue 10 (14th August 2014) - Morin, Aurélie; Letouzé, Eric; Gimenez‐Roqueplo, Anne‐Paule; Favier, Judith
<x xml:space="preserve">Abstract</x> Although the alteration of cellular metabolism in cancer was reported by Warburg in the early 1930s, a regain of interest in cancer metabolism has more recently followed the discovery of germline or somatic mutations in genes coding for metabolic enzymes (succinate dehydrogenase, fumarate hydratase and isocitrate dehydrogenase) that are associated with tumor susceptibility. Mutations in these genes are found in numerous tumor types including paragangliomas, kidney cancers, leiomyomas, glioblastomas and acute myeloid leukemia. They lead to the accumulation of so‐called oncometabolites that behave as competitors of 2‐oxoglutarate‐dependent dioxygenases, involved in a broad spectrum of pathways such as hypoxic response and epigenetic reprogramming. Here, we review the diverse pathways affected by oncometabolites, their potential role in cancer formation, maintenance, metastasis and sensitivity to chemotherapies, as well as emerging new therapeutic strategies.